(untitled) (Global Journal of Management and Business Research, 2023)
The article examines a number of propositions of the Ahangyol theory proposed by the author in the field of management of business entities The theory is gaining increasing recognition in the scientific world these days Proposals are made on the main conditions for creating a harmonious situation in a business entity and how to meet these conditions Using the 4-energy provision of the Ahangyol theory the author identifies he key components for the existence and operation of each business entity The proposed mathematical model can help reveal the latent factors that cause failures of business entities Keywords business entity management Ahangyol system power energy latent opportunities